3D hydrogeological modelling at a mining development site with complex hydrostratigraphy in northern Finland - Åberg, Susanne (Helsingin yliopisto, 2021)
There is an increase in mining projects in northern regions in the areas of complex Quaternary sediments overlaying weathered bedrock, where groundwater systems are understudied. This study increase the understanding of the interaction of surface and groundwaters in an ecologically sensitive northern area where mining and other human activities occur. Groundwater and surface water interactions in riverbanks and open mire areas are critical environments of groundwater-dependent ecosystems (GDEs). Mires are a prevailing feature in northern boreal and subarctic regions, and their interactions with groundwater and other surface water systems are usually poorly understood. If nutrient-rich fens are located in an area where mining activities are planned to take place, a detailed understanding of the water balance and groundwater discharge and recharge patterns are needed, especially how groundwater is linked to properties of the subsurface sediments. Northern areas glaciated and located in weak glacial erosion areas during the last ice ages, could form a complex sedimentary succession interlayered with low-conductivity till and variable sorted sediments having hydraulic conductivity that is orders of magnitudes higher. The glacial–interglacial cycles can enable the formation of highly heterogeneous and scattered sediment units, which are challenging to model. The study area is located in the western part of a Natura 2000-protected Viiankiaapa mire, which lies above a high-grade and significant Ni-Cu-PGE deposit. The hydrology of the regulated River Kitinen nearby affects the western part of the Viiankiaapa mire, presumable supporting the habitats of groundwater-influenced mire species. The construction of hydroelectric power plants and river regulation have changed the hydrology of the study area from the 1970s onwards. The first objective of this study was to 1) characterize the groundwater recharge/discharge and flow patterns of groundwater in Quaternary sediments and shallow bedrock, 2) examine the effect of ...